Handbook of research on economic and political implications of green trading and energy use - Das, Ramesh Chandra, 1973- (Advances in finance, accounting, and economics (AFAE) book series., 2019)
"This book examines the economic and political aspects of green trading and energy use from a global perspective. It also highlights the issues related to carbon trading, carbon credit, diplomatic conflicts in implementing environmental policies, energy use and energy efficiency, and the impact of these factors on economic outputs"--